The relationship between job satisfaction and intention to leave at Mechanical Handling Engineering (MHE)-Demag Malaysia Sdn Bhd - Priya, Kasavan (2015)
The purpose of this research was to investigate the different aspects of job satisfaction mainly on intrinsic and extrinsic that impacts the MHE-Demag employees which eventually led to high turnover rate. In short, to determine and measure the factors that lead to job satisfaction and job dissatisfaction and to present findings and make recommendations to promote/improve job satisfaction in the mentioned organization. The data for this research was collected and administered by means of a structured questionnaire based on the Minnesota Job Satisfaction Questionnaire (MSQ). It was discovered that most of the employees drew a lower job satisfaction from the absence of career development, interpersonal relationship and decision making compared to other aspects of job satisfaction such as remuneration and the benefit that they receive, general working environment, the ability to work independently and etc. in overall. Hence, it was found that employees were generally dissatisfied with their jobs in this relevant organization with the high possibility of either to leave or quit in long term, in other words